Nostalgia as a psychological resource for people with dementia: A systematic review and meta-analysis of evidence of effectiveness from experimental studies. (February 2020) - Umar Ismail, Sanda; Cheston, Richard; Christopher, Gary; Meyrick, Jane
Objective: This review systematically examines evidence relating to the effect of nostalgia on psychological well-being through a meta-analysis of measures of social connectedness, self-esteem, meaning in life, self-continuity, optimism and positive and negative affect. Rationale: If nostalgia is to be used as a clinical intervention to boost well-being in dementia by reducing threat, then it is important to assess its therapeutic potential. Results: Searches carried out in July 2014 and updated in February 2018 identified 47 eligible experimental studies comparing nostalgic reminiscence and non-nostalgic reminiscence to be included in the meta-analysis. Nostalgic reminiscence had moderate effects on positive affect (0.51 (0.37, 0.65), p = 0.001), social connectedness (0.72 (0.57, 0.87), p = 0.001), self-esteem (0.50 (0.30, 0.70), p = 0.001), meaning in life (0.77 (0.47, 1.08), p = 0.001) and optimism (0.38 (0.28, 0.47), p = 0.001) and a large effect on self-continuity (0.81 (0.55, 1.07), p = 0.001). There was, however, no difference between the effect of nostalgic reminiscence and non-nostalgic reminiscence for negative affect (−0.06 (−0.20, 0.09), p = 0.443). Conclusion: This systematic review and meta-analysis provides an overview of the evidence base for nostalgia. This is an important stage in developing nostalgia as a clinical intervention for people with dementia which might be achieved, for instance, by adapting current reminiscence and life review techniques. This meta-analysis will therefore also serve as a valuable reference point for the continued exploration of nostalgia as an intervention.